Unsymmetrically pyrazole-3-carboxylic acid substituted phthalocyanine-based photoanodes for use in water splitting photoelectrochemical and dye-sensitized solar cells - KOCA, ATIF (PERGAMON-ELSEVIER SCIENCE LTD, 2019)
A new photosensitizer, PCA-ZnPc-2, was synthesized through the asymmetric functionalization of phthalocyanine ring with a pyrazole-3-carboxylic acid as the electron-withdrawing and anchoring group and six hexylsulfanyl as the bulky electron-donating groups. PCA-ZnPc-2 was tested in dye-sensitized solar cells (DSSCs) and its performance was compared with PCA-ZnPc-1. It was found that PCA-ZnPc-2 has higher electron-donating ability which is favorable for light harvesting and suppress the dye aggregation on TiO2 when compared to PCA-ZnPc-1. Also, the new photosensitizer was used in dye-sensitized photoelectrochemical cells for hydrogen production under visible irradiation. The results show that PCA-ZnPc-2 is a promising photosensitizer to harvest the red/near-IR regions.
Keywords: Phthalocyanine; Pyrazole-3-carboxylic acid; Dye-sensitized solar cells; Photoelectrochemical hydrogen production; ZINC PHTHALOCYANINE; PHOTOVOLTAIC PERFORMANCE; ANCHORING GROUPS; TIO2; COADSORBENT; EFFICIENCY; CONVERSION; STRATEGY; CARBON; FILM